Variation in electrode redox potential selects for different microorganisms under cathodic current flow from electrodes in marine sediments - Bonita R. Lam; Annette R. Rowe; Kenneth H. Nealson (Environmental Microbiology, 2018)
Summary Extracellular electron transport (EET) is a microbial process that allows microorganisms to transport electrons to and from insoluble substrates outside of the cell. Although progress has been made in understanding how microbes transfer electrons to insoluble substrates, the process of receiving electrons has largely remained unexplored. We investigated redox potentials favourable for donating electrons to dissolved and insoluble components in Catalina Harbor marine sediment by combining electrochemical techniques with geochemistry and molecular methods. Working electrodes buried in sediment microcosms were poised at seven redox potentials between −300 and −750 mV versus Ag/AgCl using a three‐electrode system. In electrode biofilms recovered after 2‐month incubations, overall community diversity increased with more negative redox potentials. Abundances of known EET‐capable groups (e.g., Alteromonadales and Desulfuromonadales ) varied with redox potential. Motility and chemotaxis genes were found in greater abundance in electrode communities, suggesting a possible selective advantage of these pathways for colonization and utilization of the electrode. Our enrichments demonstrated the validity of this approach in capturing groups known, as well as novel groups (e.g., Campylobacterales ) that perform EET. The diverse nature of the enriched cathode communities suggest that insoluble substrate oxidation may be a critical, although poorly described microbial metabolic process in marine sediment.

In situ electrochemical enrichment and isolation of a magnetite‐reducing bacterium from a high pH serpentinizing spring - Annette R. Rowe; Miho Yoshimura; Doug E. LaRowe; Lina J. Bird; Jan P. Amend; Kazuhito Hashimoto; Kenneth H. Nealson; Akihiro Okamoto (Environmental Microbiology, 2017)
Summary Serpentinization is a geologic process that produces highly reduced, hydrogen‐rich fluids that support microbial communities under high pH conditions. We investigated the activity of microbes capable of extracellular electron transfer in a terrestrial serpentinizing system known as ‘The Cedars’. Measuring current generation with an on‐site two‐electrode system, we observed daily oscillations in current with the current maxima and minima occurring during daylight hours. Distinct members of the microbial community were enriched. Current generation in lab‐scale electrochemical reactors did not oscillate, but was correlated with carbohydrate amendment in Cedars‐specific minimal media. Gammaproteobacteria and Firmicutes were consistently enriched from lab electrochemical systems on δ‐MnO 2 and amorphous Fe(OH) 3 at pH 11. However, isolation of an electrogenic strain proved difficult as transfer cultures failed to grow after multiple rounds of media transfer. Lowering the bulk pH in the media allowed us to isolate a Firmicutes strain ( Paenibacillus sp .). This strain was capable of electrode and mineral reduction (including magnetite) at pH 9. This report provides evidence of the in situ activity of microbes using extracellular substrates as sinks for electrons at The Cedars, but also highlights the potential importance of community dynamics for supporting microbial life through either carbon fixation, and/or moderating pH stress.